2017
DOI: 10.1155/2017/5706152
|View full text |Cite
|
Sign up to set email alerts
|

Aloperine Protects Mice against DSS-Induced Colitis by PP2A-Mediated PI3K/Akt/mTOR Signaling Suppression

Abstract: Colitis is a major form of inflammatory bowel disease which involved mucosal immune dysfunction. Aloperine is an alkaloid isolated from the shrub Sophora alopecuroides L. and has been recognized as an effective treatment for inflammatory and allergic diseases. The present study aimed to examine the molecular mechanisms underlying aloperine-mediated colitis protection. We found that aloperine treatment improved colitis induced by dextran sodium sulfate (DSS) based on body weight, disease activity index, colonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 46 publications
2
33
0
1
Order By: Relevance
“…Similarly, several other alkaloids have been shown to reduce PI3K signaling cascades in the DSS mouse model of colitis. For example, quinolizidine alkaloids oxymatrine and aloperine ameliorate DSS colitis by inhibiting the PI3K/Akt pathway and T-cell responses [ 61 , 62 ]. Plant-derived alkaloids evodiamine and rutaecarpine inhibit corticosterone production by decreasing the activity of cAMP-related pathways in rat zona fasciculata–reticularis cells [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several other alkaloids have been shown to reduce PI3K signaling cascades in the DSS mouse model of colitis. For example, quinolizidine alkaloids oxymatrine and aloperine ameliorate DSS colitis by inhibiting the PI3K/Akt pathway and T-cell responses [ 61 , 62 ]. Plant-derived alkaloids evodiamine and rutaecarpine inhibit corticosterone production by decreasing the activity of cAMP-related pathways in rat zona fasciculata–reticularis cells [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical studies, LB-100 was shown to inhibit proliferation and induce apoptosis in a variety of cultured cancer cells. LB-100 also acts as an effective chemo-and radiosensitizer for the treatment of various cancers, and LB-100 exhibited potent in vivo antineoplastic activity in combination with cisplatin or doxorubicin in mouse xenograft models (21,23,25,27,80,81). The first-in-human phase I trial (NCT01837667) recently concluded that the safety, tolerability, and preliminary evidence of antitumor activity support the continued development of LB-100 Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…In nearly all reports describing LB-100 activity, the target of LB-100 is ascribed to the specific inhibition of ser/thr protein phosphatase type 2A (PP2A; refs. 21,23,25,27,80,81). However, the most cited reference to support selectivity for PP2A (22) was corrected in 2009, revealing that the compound with >10,000-fold selectivity for PP2A was another endothall derivative [LB-102; 4-(3-carboxy-7-oxa-bicyclo [2.2.1] heptane-2-carbonyl)piperazine-1-carboxylic acid tert-butyl ester; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori can promote an inflammatory response during infection, which is regulated through c-Met/PI3K/Akt/mTOR signaling pathway activation [ 33 ]. Aloperine regulates the inflammatory response in colitis through inhibiting the PI3K/Akt/mTOR signaling pathway in a protein phosphatase 2A-dependent manner [ 34 ]. Our results showed that up to seven genes that were upregulated participated in the PI3K/Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%